2021
DOI: 10.1038/s41598-021-94994-9
|View full text |Cite
|
Sign up to set email alerts
|

Insights into non-autoimmune type 1 diabetes with 13 novel loci in low polygenic risk score patients

Abstract: With polygenic risk score (PRS) for autoimmune type 1 diabetes (T1D), this study identified T1D cases with low T1D PRS and searched for susceptibility loci in these cases. Our hypothesis is that genetic effects (likely mediated by relatively rare genetic variants) of non-mainstream (or non-autoimmune) T1D might have been diluted in the previous studies on T1D cases in general. Two cohorts for the PRS modeling and testing respectively were included. The first cohort consisted of 3302 T1D cases and 6181 controls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In both the previous reports [ 20 , 25 ], BMI/T2D-associated SNPs with genome-wide significance (i.e., P ≤ 5E−08) were used as the instrumental variables (IVs). According to our study, the overall genetic risk of a complex disease/trait may be better captured at the cutoff of P-value ≤ 1E−05, while stricter cutoff may cause the missing of informative SNPs, and looser may introduce noise by including SNPs with spurious association [ 26 ]. Could the null effect of T2D be due to missing genetic information?…”
Section: Discussionmentioning
confidence: 99%
“…In both the previous reports [ 20 , 25 ], BMI/T2D-associated SNPs with genome-wide significance (i.e., P ≤ 5E−08) were used as the instrumental variables (IVs). According to our study, the overall genetic risk of a complex disease/trait may be better captured at the cutoff of P-value ≤ 1E−05, while stricter cutoff may cause the missing of informative SNPs, and looser may introduce noise by including SNPs with spurious association [ 26 ]. Could the null effect of T2D be due to missing genetic information?…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, the present study found that hsa-miR-98–5p was sponged by the LINC02432 and regulated HK2 in PAAD cells. To our knowledge, LINC02432 had only been reported to be highly expressed in the kidney and pancreas ( Fagerberg et al, 2014 ; Qu et al, 2021 ). There was no report about the function of LINC02432.…”
Section: Discussionmentioning
confidence: 98%
“…Associations with alleles and amino acids in the HLA region were estimated using stepwise logistic regression, as previously described [19]. Second, we used PRSice-2 in the tuning set [51,56,57] to select a set of SNPs to include in the PRS using clumping and thresholding. Clumping refers to a procedure in which the most significant of two correlated SNPs (r 2 > 0.1)in a window of size 250 kbp-is kept, whereas the rest is discarded [58].…”
Section: Clumping and Thresholdingmentioning
confidence: 99%